Study on influence of bedding on hydraulic fracture propagation morphologies in Jurassic reservoirs - YUAN Lina, WANG Guangtao, WANG Chengwang, HOU Rui, SUN Feng (Youqicang pingjia yu kaifa)
The Jurassic formations of the Ordos Basin, with burial depths ranging from 300 to 2,200 m, exhibit numerous horizontal bedding planes within the reservoirs, leading to complex variations in fracture morphology and propagation direction during hydraulic fracturing. Laboratory Brazilian splitting tests were conducted to evaluate the tensile strength of core samples from Jurassic formations, considering the impact of bedding. The tensile strength differences between specimens perpendicular to and parallel to bedding planes were compared. Based on the experimental data, a three-dimensional finite element model using the cohesive element method was developed to characterize hydraulic fracturing in multilayered Jurassic reservoirs, focusing on the effects of bedding strength and in-situ stress differences on fracture morphology and propagation paths. The results indicated that bedding strength and stress differences were the primary factors influencing fracture deflection. High bedding strength and large stress differences reduced the restraining effect of bedding on fractures, enhancing their vertical penetration across layers. Conversely, low bedding strength and small stress differences led to the opening of bedding planes, causing fractures to deviate and propagate along bedding surfaces. These findings provide guidance for optimizing hydraulic fracturing operations in Jurassic reservoirs.